Karakterisasi Silikon dari Sekam Padi Terdoping dengan Kobalt: Analisis Struktur dan Sifat Magnetoelektrik - Kurniawan, Rizky; Andriayani, Andriayani; Gea, Saharman; Kurniawan, Hadi (Jurnal Ilmu Fisika, 2024)
The development of Si-based materials has attracted increasing attention, particularly for application in semiconductors, batteries, sensors, and optical technology. Silicon has abundant availability, high energy storage capacity, and low work potential. However, it faces compatibility challenges due to its low electrical conductivity and extremely small magnetic susceptibility. This research aimed to investigate the influence of Co dopants on the structure, morphology, electrical conductivity, and magnetic susceptibility of silicon. Silicon was synthesized using the magnesiothermic reduction method, and silicon was modified with Co metal dopants at 0.1% and 0.5% concentrations through the impregnation method. XRD analysis results showed that Si, 0.1% Co/Si, and 0.5% Co/Si exhibit silicon diffraction patterns at 2θ = 28.42º; 47.28º; 56.11º; 69.13º; and 76.36º. The morphology of Si and Co/Si revealed a rough, uneven, and porous surface with particles appearing spherical. Electrical conductivity increases with Co concentration: Si = 1223 µS/cm, 0.1% Co/Si= 1376 µS/cm, and 0.5% Co/Si= 1529 µS/cm. Magnetic susceptibility measurements indicated that Si, 0.1% Co/Si, and 0.5% Co/Si are paramagnetic at a range of 1.18 x10-6 to 1.25 x10-5 SI. These characterization results confirmed that the modification with Co dopants can enhance the magnetoelectric properties of silicon.